Pemindahan haba konjugat; cecair nano; FEM; fotovoltaik; sistem terma Pemindahan haba konjugat; cecair nano; FEM; fotovoltaik; sistem terma Pemindahan haba konjugat; cecair nano; FEM; fotovoltaik; sistem terma - Ike, Ubadinanwa Elvis; Ike, Charles Chinwuba (Penerbit Universiti Kebangsaan Malaysia, 2023)
In a bid to minimize the adverse effects of agricultural waste materials in the environment and also encourage for its optimal usage, this study aims at developing model constants for optimizing the California Bearing Ratio (CBR) of Lateritic Soils stabilized with Rice Husk Ash (RHA) using Scheffe’s method. The study practically involved sampling of the materials, laboratory testing and model formulation. The natural soil was subjected to standardized laboratory testing to determine its index and Engineering properties. The scheffe’s method provided mix ratios for the three mix components (lateritic soil, RHA and water) involved in the mix design. The method also employs the use of second-degree polynomials to generate the model constants. The CBR of the soil was the primary property of the soil considered in the study therefore, a CBR test was conducted on the natural soil and modified soil. The optimization technique carried out gave an optimal mix observed to be of mix ratio 1: 1.70: 0.25 for lateritic soil, RHA and water with a CBR value of 30%. The model formulated was further subjected to validation using the F-test and T-test statistical method and it was found adequate at a confidence level of 95%. Hence, the null hypothesis (H0 ) was adopted. The formulated model being adequate can be used exclusively to predict the CBR of Lateritic soil Stabilized with Rice Husk Ash within the same locality.